Mathematical Problem-Solving Skill Profile Based on Matematical Proficiency Level - Musodiqoh, Ummu Atiyatul; Jaelani, Anton (Proceedings Series on Social Sciences & Humanities, 2025)
Mathematical problem-solving skillsare important for students to have as part of mastering mathematical competencies. This research aims to analyze students' mathematical problem-solving skillsat at one of the state high schools in Mesuji Raya based on their level of mathematical proficiency. The research subjects were students selected based on high, medium and low levels of mathematical ability. This qualitative research method uses mathematical problem-solving instruments and in- depth interviews. Data analysis consists of data reduction, data categorization, data interpretation, and drawing conclusions. The research results show that there are significant variations in students' skillsat each level of mathematical proficiency. Students with high mathematical skillsare able to understand problems, relate concepts to real contexts, and evaluate solutions well. On the other hand, students with medium ability experience difficulty in applying problem solving strategies effectively, while students with low ability show weaknesses in almost all stages of problem solving.